Internalizing Financial Literacy Culture through Project-Based Experiential Learning: Evidence from Indonesian University Students - Stella Melin; Gumarus Satriawisti; Agusandi Agusandi; Samuel Samuel (Yayasan Vifada Cendikia Indonesia, 2026)
Financial literacy has become an essential competency for university students in responding to increasingly complex financial environments. Nevertheless, financial education is still predominantly delivered through theoretical instruction, resulting in limited behavioral changes in everyday financial practices. This study explores how financial literacy culture is internalized through project-based experiential learning among university students. Employing an exploratory qualitative approach with Reflexive Thematic Analysis, the study involved 50 students who participated in a semester-long saving and investment project. Data were collected through in-depth interviews and reflective storytelling and analyzed using the six-stage framework proposed by Braun and Clarke. The analysis identified six interconnected themes: (1) financial literacy as a new experience, (2) transformation of awareness toward the value of money, (3) consistency as the primary challenge in developing financial behavior, (4) the emergence of financial security through emergency savings, (5) continuation of saving and investment behavior, and (6) internalization of financial literacy culture through experiential learning. The findings demonstrate that direct financial experience not only improves students’ financial knowledge but also reshapes their attitudes, strengthens self-control, encourages long-term financial planning, and fosters continued financial behavior. The study contributes to the development of experiential learning as an effective pedagogical approach for strengthening financial literacy culture among university students.